2011
DOI: 10.1016/j.visres.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Testing dynamical models of vision

Abstract: Most models of vision focus either on the spatial or temporal aspects of visual processing and neglect the other component. A variety of studies have shown, however, that spatial and temporal processing cannot easily be separated. The shine-through effect has proven to be a sensitive tool to study spatio-temporal processing. Two very different dynamical models, the 3D-LAMINART and the WCTM model, have explained the key aspects of the shine-through effect. Based on computer simulations Francis (2009) proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…However, if masked with a grating of seven or more straight lines, the vernier target is more easily perceived, and “shines through” the grating. The 3D-LAMINART (Grossberg, 1997 ; Francis, 2009 ) and WCTM (Herzog et al, 2003 ) computational models have been able to reproduce some but not all aspects of these phenomena (Rüter et al, 2011 ). 3D-LAMINART is a general purpose visual model that utilizes binocular vision to perceive the vernier target.…”
Section: Introductionmentioning
confidence: 99%
“…However, if masked with a grating of seven or more straight lines, the vernier target is more easily perceived, and “shines through” the grating. The 3D-LAMINART (Grossberg, 1997 ; Francis, 2009 ) and WCTM (Herzog et al, 2003 ) computational models have been able to reproduce some but not all aspects of these phenomena (Rüter et al, 2011 ). 3D-LAMINART is a general purpose visual model that utilizes binocular vision to perceive the vernier target.…”
Section: Introductionmentioning
confidence: 99%
“…However, purely spatial approaches to vision or purely temporal approaches to vision are insufficient, as they cannot be easily separated. 31 Furthermore, it has been argued that nontimed VA tests may not reflect the demands in activities of daily life. 32 Studies on visual processing speed in older adults have revealed that slower visual processing is related to an elevated risk of at-fault traffic accidents and decreased performance on other aspects of daily living (for an overview, see, e.g., Refs.…”
mentioning
confidence: 99%